Labor-saving agricultural mechanization services and the technical efficiency in agricultural production: evidence from Chinese rural households - Yangchen, Danny Cyra; Yang, Qisong; Hong, Mingyong (Frontiers in Sustainable Food Systems, 2025)
IntroductionIn the context of accelerating industrialization and urbanization, China’s agricultural production faces challenges such as labor shortages and fragmented land supply. Labor-saving agricultural mechanization services (LAMS) have emerged as a scalable factor innovation to address such issues. However, the efficiency implications and moderating factors of LAMS adoption remain insufficiently understood.MethodsUsing 2019 cross-sectional survey data from 1,519 medium indica rice growers in China, this study investigates the impact of LAMS adoption on technical efficiency (TE) using a stochastic frontier analysis (SFA) approach. To address endogeneity concerns, a two-stage least squares (2SLS) instrumental variable strategy is employed. Moderating effect models further identify causal effects of market- and policy-based factors.ResultsThe results show that LAMS adoption significantly improves technical efficiency. Market factors—measured by self-owned machinery—exhibit a substitution effect with LAMS, while policy factors—proxied by high-standard farmland construction (HSFC)—demonstrate complementary effects. Robustness checks confirm the validity of these effects across income groups.DiscussionThe findings suggest that service-based mechanization can alleviate structural constraints such as land fragmentation and labor scarcity. LAMS offer a viable pathway to enhance smallholder productivity. These insights provide valuable policy implications for agricultural transformation in land-constrained developing economies.